Effectiveness of a Food-Based Intervention to Increase Breast Milk Vitamin A Content at One Month of Infancy. (29th May 2020) - Swaminathan, Sumathi; Selvam, Sumithra; Narendra, Agnita; Thomas, Tinku; Vasudevan, Anil; Thomas, Annamma; Kurpad, Anura
Abstract: Objectives: Vitamin A requirements in early infancy are met only by breast milk intake. It is critical to ensure adequate breast milk vitamin A levels which also helps develop liver stores. The objective of the study was to evaluate the effect of a maternal food-based intervention on breast milk vitamin A content Methods: Pregnant women ( n = 50; 24 ± 1 week of gestation) were recruited for the randomized study. A 10 g of a green leafy vegetable powder (mint/coriander/curry) providing about 3200 μg β-carotene/day, for a period of 4 months up to 1 month of lactation were provided for intervention arm. Breast milk (BM) retinol concentration and BM volume were assessed. BM retinol and beta-carotene were assayed by HPLC and BM fat by creamatocrit method. BM retinol: fat ratio was calculated. The dose-to-mother deuterium dilution technique was used to estimate BM volume through enrichment of saliva measured by Fourier Transform Infrared Spectroscopy. Total BM retinol content was calculated from BM volume and the BM retinol (including beta-carotene:1 vitamin A RAE = 12 μg β-carotene). Inadequacy of intake was defined as proportion of infants with intake below a requirement of 400 μg RAE/day. Analysis of co-variance was performed after adjusting for age of mother, change in maternal blood retinol from baseline and BM fat, to compare outcomes between intervention and control arm. Results: Maternal age, gestational age, socio-demographic characteristics and baseline vitamin A intake were comparable in both arms. Mean BM volume was similar in the 2 arms (676 ± 102 in intervention vs 630 ± 100 ml/day in control). BM retinol content (0.72 ± 0.12 vs 0.64 ± 0.11 μg/mL; P = 0.029) and BM retinol: fat ratio [0.41 (0.31, 0.47) vs 0.29 (0.21, 0.41), P = 0.011] were significantly higher in the intervention arm. The mean total BM retinol content was significantly higher in the intervention (482.2 ± 100.7 vs 406.5 ± 89.2 μg/day; P = 0.015; Cohen's effect size 0.80). Inadequacy of infant vitamin A intake was 14.3% in the intervention arm as against 39.1% in the control arm ( P = 0.065). Conclusions: The food-based intervention was effective in increasing vitamin A content in breast milk and thereby vitamin A intake in infants. Funding Sources: International Atomic Energy Agency.